Colibacillosis in Chickens: Etiology, Pathology and Control - Tarmudji . (Indonesian Center for Animal Research and Development, 2003)
Colibacillosis in poultry is an infectious disease of birds in which Escherichia coli is the primary or secondary pathogen. The disease affects broiler and layer of all age groups, but is more frequent in young than mature. Many outbreaks occur in poultry raised under low standard of sanitation, poor environmental conditions or after a respiratory or immunosuppressive disease. There are three serotypes of E. coli, O1:K1, O2:K1 and O78: K80, and other serotypes that have been identified in organs of sick birds, feed, drinking water and litter from farms in the area of Java and Bali. E. coli is present in normal intestines of bird and is distributed widely in faeces. Birds are continuously exposed through contaminated faeces, water, dust and environment. Diagnosis of colibacillosis is based on clinical picture, pathognomonic lesions (septichemia, airsacculitis, pericarditis and perihepatitis) and isolation of E. coli. Outbreaks are usually as the result of a combination of etiological factors including the presence of other infections such as Swollen Head Syndrome (SHS), Chronic Respiratory Disease (CRD), Newcastle Disease (ND), etc. Treatments are usually effective if given early and antibiotic sensivity testing is advised where applicable. To prevent Coli bacterial infection should be taken on an improved farm management. Hatchery sanitation/ desinfection procedure should be practiced. Vacination program is undertaken to protect against immunosuppressive and respiratory disease. Key words: Colibacillosis, poultry, etiology, pathology, control